2021
DOI: 10.1038/s41366-021-00957-5
|View full text |Cite
|
Sign up to set email alerts
|

The postnatal leptin surge in mice is variable in both time and intensity and reflects nutritional status

Abstract: Background/objectives The murine postnatal leptin surge occurs within the first 4 weeks of life and is critical for neuronal projection development within hypothalamic feeding circuits. Here we describe the influence of nutritional status on the timing and magnitude of the postnatal leptin surge in mice. Methods Plasma leptin concentrations were measured 1–3 times per week for the first 4 weeks of life in C57BL/6J pups reared in litters adjusted to 3 (smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 71 publications
3
22
0
Order By: Relevance
“…There is strong evidence that maternal HFD feeding during perinatal period as well as overnutrition of sucking pups (by decreasing litter size) increases body weight and predisposes the offspring to greater weight gain when exposed to HFD in adulthood (Ainge et al, 2011;Lagisz et al, 2015;Ribaroff et al, 2017). Some of the leptin-related consequences of overfeeding in rodents are related to the magnitude of the postnatal leptin surge (Marangon et al, 2020;Skowronski et al, 2021), leptin sensitivity in the CNS (Kirk et al, 2009), neuroanatomy of the leptin-dependent feeding circuits (Kirk et al, 2009;Vogt et al, 2014), and epigenetic changes-specifically hypermethylation of the hypothalamic POMC promoter (Plagemann et al, 2009;Marco et al, 2014).…”
Section: The Intrauterine Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There is strong evidence that maternal HFD feeding during perinatal period as well as overnutrition of sucking pups (by decreasing litter size) increases body weight and predisposes the offspring to greater weight gain when exposed to HFD in adulthood (Ainge et al, 2011;Lagisz et al, 2015;Ribaroff et al, 2017). Some of the leptin-related consequences of overfeeding in rodents are related to the magnitude of the postnatal leptin surge (Marangon et al, 2020;Skowronski et al, 2021), leptin sensitivity in the CNS (Kirk et al, 2009), neuroanatomy of the leptin-dependent feeding circuits (Kirk et al, 2009;Vogt et al, 2014), and epigenetic changes-specifically hypermethylation of the hypothalamic POMC promoter (Plagemann et al, 2009;Marco et al, 2014).…”
Section: The Intrauterine Environmentmentioning
confidence: 99%
“…In rats and mice (Marangon et al, 2020;Skowronski et al, 2021), maternal high fat diet (HFD) feeding during gestation and/or lactation, or overfeeding the pups via reduced litter size augments the postnatal leptin surge (see below) and subsequent weight in the offspring. Caloric or protein restriction of dams or underfeeding the pups by increased litter size reduces and delays the leptin surge with a reduction in weight into adulthood (Delahaye et al, 2008).…”
Section: Effects Of Perinatal Leptin On Subsequent Adipositymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 ] Noteworthy, both maternal obesity and the intake of an obesogenic diet during lactation have been related to a detrimental and persistent impact on the development of the neonates. [ 6–8 ] Although the specific mechanisms involved are only partially understood, [ 9 ] milk quality may represent one of the key factors. [ 10 ] Thus, intervention studies in rodents have shown that the intake of an obesogenic diet during the perinatal period negatively affects the structure and function of the mammary gland and therefore the composition of milk, [ 11 ] including altered metabolism‐regulating hormones and fatty acids (FA) profiles.…”
Section: Introductionmentioning
confidence: 99%
“… 40 The resultant exposure of the PWS foetus to a restricted nutritional environment we suggest may impact on subsequent leptin-induced foetal hypothalamic development pre- and post-natally, which has been shown to be dependent on nutritional status. 41 , 42 These hypotheses require further study in animal models of PWS and where possible longitudinally in humans, and here we present preliminary evidence in young adults of hypothalamic dysfunction.…”
Section: Discussionmentioning
confidence: 65%